PENGARUH PEMBELAJARAN E-LEARNING TERHADAP TINGKAT PEMAHAMAN SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 KOTA JAMBI - Agustin, Indah Dwi; Sari, Pratiwi Indah (Universitas Batanghari Jambi, 2021)
AbstractThis study aims to determine (1) the description of e-learning and the level of understanding of students in class XI IPS on economics subjects at SMA Negeri 1 Jambi City. (2) the effect of e-learning on the level of understanding of class XI IPS students on economics subjects at SMA Negeri 1 Jambi City. This research design uses quantitative research methods, with data collection techniques through observation, interviews, and questionnaires. Where the population in this study were 143 students with a sample of 106 students. The research instrument test technique used in this study is the validity and reliability test, while the classical assumption test used is Descriptive Analysis, Normality Test, Homogeneity Test, and Simple Regression Test. The results showed that (1) e-learning was included in the very poor category with an average TCR value of 49.52%, and the level of student understanding of 66.25% in the fairly good category. (2) E-learning has an influence on the level of understanding which can be seen from tcount > ttable of 2.024 > 1.658. So, Ha is accepted and Ho is rejected. That is, if the use of e-learning is carried out well in schools, it can train students' independence in the teaching and learning process, and the level of student understanding will be better if students can understand a material using e-learning.Keywords: E-Learning Learning, Level of Understanding